Understanding innovation: The development and scaling of orange-fleshed sweetpotato in major African food systems - Low, Jan W.; Thiele, Graham (Elsevier, 2020)
The development and scaling of orange-fleshed sweetpotato (OFSP) during the past 25 years is a case study of a disruptive innovation to address a pressing need – the high levels of vitamin A deficiency among children under five years of age in sub-Saharan Africa. When the innovation was introduced consumers strongly preferred white or yellow-fleshed sweetpotato, so it was necessary to create a demand to respond to that need. This was at odds with the breeding strategy of responding to consumers’ demands. Additional elements of the innovation package include seed systems and nutrition education to create the awareness amongst consumers of the significant health benefits of OFSP. Complementary innovation is required in promotion and advocacy to ensure a supportive institutional environment.